DINAMIKA PERKEMBANGAN PARIWISATA DI DESA PAKRAMAN UBUD - Adiprana, I Putu Gatot; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 1 No 1 (2013): VOL 1, NO 1 (2013): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2013.v01.i01.p04, 2013)
ABSTRACT The development of Ubud Pakraman was really fast, especially in terms of the ability to anticipate the opportunities that come to Ubud region, which indicates the very dynamic community. The dynamics can be shown by the emergence of various movements towards economical and practical. However in the religious life that is ingrained in the structure of people's lives in Ubud is still strong and still function properly in the middle phase change from traditional to post a traditionalist.  The limit of the scope of this study discusses the process of development of rural tourism in Ubud Pakraman, of course, in the process of the development of socio-cultural changes that occur before and after the inclusion of tourism.  The results of this study indicate that there though characteristics or attitudes and new practices in the context of traditional.
Keywords: Key words: The development,socio-cultural changes,Ubud Pakraman